2011
DOI: 10.1021/nn102295p
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmonic Effects of Metallic Nanoparticles on the Performance of Polymer Bulk Heterojunction Solar Cells

Abstract: We have systematically explored how plasmonic effects influence the characteristics of polymer photovoltaic devices (OPVs) incorporating a blend of poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl-C(61)-butyric acid methyl ester (PCBM). We blended gold nanoparticles (Au NPs) into the anodic buffer layer to trigger localized surface plasmon resonance (LSPR), which enhanced the performance of the OPVs without dramatically sacrificing their electrical properties. Steady state photoluminescence (PL) measurements rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
760
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,000 publications
(783 citation statements)
references
References 60 publications
18
760
2
3
Order By: Relevance
“…7b the increase in the EQE via incorporating the 15% Au NRs in ABL solution. We found that the EQE was enhanced by up to 12-14% respectively around 520-640 nm, which are near to the transverse absorption reported results similar to ours with the EQE curves for both reference and NPs devices having the same absorption ranges with a slight enhancement in the tail near the IR region [4,11,15].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…7b the increase in the EQE via incorporating the 15% Au NRs in ABL solution. We found that the EQE was enhanced by up to 12-14% respectively around 520-640 nm, which are near to the transverse absorption reported results similar to ours with the EQE curves for both reference and NPs devices having the same absorption ranges with a slight enhancement in the tail near the IR region [4,11,15].…”
Section: Resultssupporting
confidence: 89%
“…performance [4]. The effective reported thickness for the active layer (~ 100-200 nm) [4][5][6] is too low for a complete absorption of the incident light within the absorption range of the active layer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2d (J ph = J L −J D , where J L is the current density under illumination and J D is the current density in the dark. V eff = V o −V a , where V a is the applied voltage and V o is the voltage at which J ph is zero) [62]. The exciton dissociation probabilities (P diss ) were calculated to be 83.8%, 84.8%, 85.6%, and 87.3% for the PBDB-T:IT-M-based devices processed by XY, XY/1% ; (c) photovoltaic parameters (PCE, J sc , V oc , and FF) of PSCs processed using different solvent additives; (d) J ph versus V eff plots of the optimal devices processed using different solvent additives.…”
Section: Device Performancementioning
confidence: 99%
“…[32][33][34] On the contrary, in dense particle films the absorption of previous studies. 35,36 The lower PL quenching can be attributed to the strong local electric field at the particles' vicinity which promotes the exciton dissociation. [32][33][34] Furthermore, the high density of particles with small separation distances causes an extra shadowing effect, undesirable for high efficiency photovoltaics.…”
mentioning
confidence: 99%